PENGARUH MEDIA AUDIOVISUAL MELALUI MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS OLEH SISWA - DIYAN FIRMANSYAH; Darlen Sikumbang; Rini Rita T. Marpaung (Universitas Lampung, 2013)
Two elements that very important in the learning process are model and media instructional. The observation was known that teachers not give an opportunity for students to develop independently so that students' critical thinking skills are underdeveloped. This study aimed to determine the effect of the use of audiovisual media through PBL models in improving critical thinking skills by students. The research design was pretest posttest equivalent group. The research sample class X2 and X5 are selected by cluster random sampling. The results showed that the use of audiovisual media through PBL models can improve critical thinking skills by students with average pretest (20.45), posttest (73.13), and N-gain (0,66). The average percentage of students also increased activity in all aspects of that observed with good criterion (85.04). In addition, the majority of students (89.68%) gave positive response about the use of audiovisual media through PBL models. Thus, we can conclude the use of audiovisual media through PBL models have a significant effect in improving critical thinking skills by students in the subject matter of environmental pollution and preservation efforts. Keywords: PBL models, audiovisual media, critical thinking skills, environmental pollution and preservation efforts.